Malaysia facing threats from local militants, foreign extremist students - Daily Express, (KK) (Sabah Publishing House Sdn. Bhd, 2014)
PETALING JAYA: Malaysia is facing twin threats from discontented local militants and extremist foreign students in local colleges.Prof Dr Mohd Kamarulnizam Abdullah, director of Universiti Utara Malaysia's Research Institute for Indonesia, Thailand and Singapore (UUM-ITS) said the local militants perceived that their Islamic faith was under attack while foreign students from the Middle East and African countries were using Malaysia as a safe base for their militant networks.